2010
DOI: 10.1016/j.febslet.2010.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin inhibits larval growth ofCaenorhabditis elegansthrough DAF‐16 activation

Abstract: a b s t r a c tTreatment of Caenorhabditis elegans with apigenin, 5,7,4 0 -trihydroxyflavone, induces larval growth inhibition. To understand the molecular basis of apigenin-induced larval growth inhibition, the effects of apigenin on DAF-16 activity were examined. DAF-16 was activated through nuclear translocation and the mRNA level of sod-3, one of the known DAF-16 target genes, was increased upon apigenin treatment. DAF-16 activity was required for the growth inhibition, since the larval growth retardation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Analogous results were obtained by Bartholome et al [43], where a treatment of 100  μ M EGCG for 48 h increased (2.2-fold) the amount of worms showing predominantly nuclear localisation of DAF-16 in contrast to untreated C. elegans . Similar effects were also found for quercetin [30, 36, 37], myricetin [36, 38], kaempferol, naringenin [36], fisetin [70], and apigenin [81], but not for rutin [37]. Remarkably, a 48 h pretreatment with 100 μ M quercetin enhanced the mean percentage of worms carrying predominantly nuclear DAF-16 by more than three times in contrast to untreated nematodes [30, 36, 37, 70].…”
Section: Modulation Of Representative Redox-sensitive Signalling Psupporting
confidence: 54%
See 1 more Smart Citation
“…Analogous results were obtained by Bartholome et al [43], where a treatment of 100  μ M EGCG for 48 h increased (2.2-fold) the amount of worms showing predominantly nuclear localisation of DAF-16 in contrast to untreated C. elegans . Similar effects were also found for quercetin [30, 36, 37], myricetin [36, 38], kaempferol, naringenin [36], fisetin [70], and apigenin [81], but not for rutin [37]. Remarkably, a 48 h pretreatment with 100 μ M quercetin enhanced the mean percentage of worms carrying predominantly nuclear DAF-16 by more than three times in contrast to untreated nematodes [30, 36, 37, 70].…”
Section: Modulation Of Representative Redox-sensitive Signalling Psupporting
confidence: 54%
“…In this context it was shown that Q3M increased (1.38-fold) daf-2 gene expression in the nematode compared to the control. In contrast, apigenin was found to inhibit daf-2 expression [81]. …”
Section: Modulation Of Representative Redox-sensitive Signalling Pmentioning
confidence: 99%
“…Regarding the insulin-like signalling pathway, myricetin induced an increase in nuclear DAF-16::GFP translocation (relative DAF-16::GFP localization: DMSO: 6% ± 2%; myricetin: 41% ± 7%) and a reduction in the cytosolic DAF-16::GFP fraction (DMSO: 65% ± 8%; myricetin: 30% ± 4%), respectively (Figure 5A). A nuclear translocation of DAF-16 or target gene expression was reported for different flavonoids, e.g., quercetin [28], apigenin [31], fisetin [29], kaempferol [29] and epigallocatechin-gallate [16]. A shift from cytosolic to nuclear localization of DAF-16 by myricetin (20% cytosolic compared to 70% cytosolic in control nematodes) was previously reported [20].…”
Section: Resultsmentioning
confidence: 84%
“…Among the herbal PAK1-blockers, apigenin from the CAPE-based propolis or camomile flowers is the first that has been proven to extend the lifespan of nematode (C. elegans) in a FOXO-dependent manner [14]. Apigenin is a flavonoid that blocks PAK1 by directly down-regulating PI-3 kinase [15].…”
Section: Apigeninmentioning
confidence: 99%